Multi-Functional Characteristics of the Pseudomonas aeruginosa Type III Needle-Tip Protein, PcrV; Comparison to Orthologs in other Gram-negative Bacteria - Sato, Hiromi; Frank, Dara (Frontiers in Microbiology, 2011)
Pseudomonas aeruginosa possesses a type III secretion system (T3SS) to intoxicate host cells and evade innate immunity. This virulence-related machinery consists of a molecular syringe and needle assembled on the bacterial surface, which allows delivery of T3 effector proteins into infected cells. To accomplish a one-step effector translocation, a tip protein is required at the top end of the T3 needle structure. Strains lacking expression of the functional tip protein fail to intoxicate host cells. P. aeruginosa encodes a T3S that is highly homologous to the proteins encoded by Yersinia species. The needle tip proteins of Yersinia, LcrV, and P. aeruginosa, PcrV, share 37% identity and 65% similarity. Other known tip proteins are AcrV (Aeromonas), IpaD (Shigella), SipD (Salmonella), BipD (Burkholderia), EspA (EPEC, EHEC), Bsp22 (Bordetella), with additional proteins identified from various Gram negative species, such as Vibrio and Bordetella. The tip proteins can serve as a protective antigen or may be critical for sensing host cells and evading innate immune responses. Recognition of the host microenvironment transcriptionally activates synthesis of T3SS components. The machinery appears to be mechanically controlled by the assemblage of specific junctions within the apparatus. These junctions include the tip and base of the T3 apparatus, the needle proteins and components within the bacterial cytoplasm. The tip proteins likely have chaperone functions for translocon proteins, allowing the proper assembly of translocation channels in the host membrane and completing vectorial delivery of effector proteins into the host cytoplasm. Multifunctional features of the needle-tip proteins appear to be intricately controlled. In this review, we highlight the functional aspects and complex controls of T3 needle-tip proteins with particular emphasis on PcrV and LcrV.